2021
DOI: 10.1590/s1677-5538.ibju.2019.0448
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the efficacy and tolerability of treating primary nocturnal enuresis with Solifenacin Plus Desmopressin, Tolterodine Plus Desmopressin, and Desmopressin alone: a randomized controlled clinical trial

Abstract: Introduction: Nocturnal enuresis (enuresis) is one of the most common developmental problems of childhood, which has often a familial basis, causes mental and psychological damage to the child and disrupts family solace. Objectives: In this study, we compared therapeutic effi cacy and tolerability of treating primary nocturnal enuresis (PNE) with solifenacin plus desmopressin, tolterodine plus desmopressin, and desmopressin alone. Because we don't have enough information about this comparison especially about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…The success rate of solifenacin for the treatment of NE varies from 10 % to 65 %. The CR rate of solifenacin in this study (30.0 %) was consistent with that of Ghanavati et al [4] , but lower than that of Fujinaga et al [9] . This difference may be related to short-term medication, efficacy standards and ethnic or sociocultural differences.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The success rate of solifenacin for the treatment of NE varies from 10 % to 65 %. The CR rate of solifenacin in this study (30.0 %) was consistent with that of Ghanavati et al [4] , but lower than that of Fujinaga et al [9] . This difference may be related to short-term medication, efficacy standards and ethnic or sociocultural differences.…”
Section: Resultssupporting
confidence: 91%
“…As a new generation of M-receptor blockers, solifenacin is commonly used in the treatment of overactive bladder. Studies have shown that, the application of low-dose solifenacin in pediatric PNE can effectively improve the curative effect and reduce recurrence [4] . At present, there have been some reports on the therapeutic effect of low-dose solifenacin in PNE [5] , but there are few reports on the therapeutic effect of solifenacin combined with suoquan capsules in children with PNE and further research is needed.…”
mentioning
confidence: 99%
“…Lastly, to ensure a flawless data set, we eliminated five papers that were inadvertently duplicated. Ultimately, our study comprised eight high‐quality RCTs 15,16,20–25 . The selection process is visually depicted in Figure 1, while Table 1 encapsulates the study and patient characteristics.…”
Section: Resultsmentioning
confidence: 99%
“…After receiving oral desmopressin treatment, nearly one-third of children had no subsequent MNE episodes, one-third obtained partial relief, and one-third had no benefit (7). MNE cure rate can be improved by combination therapy strategies (8).…”
Section: Introductionmentioning
confidence: 99%